PLANTS COVERING INFLUENCE TO THE RADIOISOTOPES EXISTENCE OF Cs-137 AND Pb-210 IN THE SOIL - Nita Suhartini; Barokah Aliyanta; Arief Adhari (BATAN, 2020)
PLANTS COVERING INFLUENCE TO THE RADIOISOTOPES EXISTENCE OF 137Cs and 210Pbex IN THE SOIL. Cs-137 and Pbex-210 of environmental radioisotope content in the soil can be useful to estimate the rate of erosion/deposition in an area, by comparing the inventory value of Cs-137 or Pbex-210 in observed site with those in a stable reference site. Cs-137 and Pbex-210 stick very strongly at the surface of the soil (clay), so it can use as a tracer for the movement of soil. Plants very influence the existence of Cs-137 and Pbex-210 environmental radioisotopes as a cover. If without a plant cover, then this environmental radioisotope at the soil would be gone by rain off. This experiment aims to observe the effect of plant cover on the existence of Cs-137 and Pbex-210 at the soil in uncultivated land. Sampling had been done in two uncultivated lands when the land still covering by plants (2016) and after becoming vacant land (2018), using coring (10 cm) for the surface layer and coring (7 cm) for the depth of 20 cm. The result showed that the activity of 137Cs and 210Pbex environmental radioisotopes at the surface layer decreased very significantly, and total inventory values until the depth of 20 cm decreased quite significantly at a vacant land condition. The corrosion rate for the vacant land is higher than the planted land. The value of erosion rate using the 137Cs method is 44.1 t/ha.y (CBG); -4.3t/ha.y (BMC) and 4 t/ha.y (CBG); -27.1 t/ha.y (BMC) for planted land and vacant land, respectively. Meanwhile, using the 210 Pb ex method is -8 t/ha.y (CBG); -36.9 t/ha.y (BMC) for planted land and -58 t/ha.yrs (CBG), -79.9 t/ha.yrs (BMC) for vacant land.